Chemical, Rheological and Nutritional Characteristics of Sesame and Olive Oils Blended with Linseed Oil - Fataneh Hashempour-Baltork; Mohammadali Torbati; Sodeif Azadmard-Damirchi; Geoffrey Peter Savage (Advanced Pharmaceutical Bulletin, 2018)
Purpose: Nutritional quality and oxidation stability are two main factors in the evaluation of edible oils. Oils in their pure form do not have an ideal fatty acid composition or suitable oxidative stability during processing or storage. Methods: This study was designed to evaluate the chemical, nutritional and rheological properties of oil mixtures in three ratios of olive: sesame: linseed, 65:30:5; 60:30:10 and 55:30:15. Acidity value, peroxide value, rancimat test, fatty acid profile, nutritional indexes and rheological properties of the oil blends were determined. The nutritional quality was determined by indexes, including the atherogenic and thrombogenic indexs; the ratios of hypocholesterolemic: hypercholesterolemic; poly unsaturated fatty acid: saturated fatty acid and the ω6:ω3. Results: The results indicated that blending of other vegetable oils with linseed oil could balance ω6:ω3. Results showed that formulated oils had a good balance of oxidation stability and nutritional properties as well. Rheological data showed that these oil blends followed Newtonian behavior at 4°C and 25°C. Conclusion: According to the results, addition of linseed oil to vegetable oils containing high levels of bioactive compounds was a simple and economic practice to obtain a functional oil with good nutritional and stability properties.